Effect Of Cutting Organs Of Lobster Shrimp (Cherax Quadricarinatus) On Moulting Percentage And Survival - Andriyeni Andriyeni; Zulkhasyni Zulkhasyni; Galang Samargandhi Athybi; Dedi Pardiansyah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the effect of cutting the best lobster shrimp organs on the percentage of moulting and survival of freshwater crayfish (Cherax quadricarinatus). This research was carried out from April to June 2020 at the Aquaculture Laboratory of the Faculty of Agriculture, Prof. University. Dr. Hazairin, SH Bengkulu. The research was carried out for 60 days. The container used is a plastic basket measuring 29 cm long, 19 cm wide and 11 cm high as many as 20 units. The number of lobsters used for each container is 3 tails, with an initial average length of 9-12 cm/head and an initial average weight of 25-50 grams/head. The design used was a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were P1 = No Cutting (Normal), P2 = Swimming Leg Cut, P3 = Claw Cutting, and P4 = Eye Cut (Ablation). Data were analyzed by means of variance (Analysis of Variance) with a test levels of 5% and 1%. If it has a significant effect, then it is continued with the BNT test (Least Significant Difference) with a test level of 5%. The parameters observed were the percentage and survival. The results showed that cutting the organs of freshwater crayfish (Cherax quaddricarinatus) had a very significant effect on the percentage of moulting, but had no significant effect on survival. The best organ cutting is found in the claw cutting experiment with a moulting percentage of 60%. The survival of all the treatments tried was between 73%-93%.